Inhibition of Autophagic Turnover in β-Cells by Fatty Acids and Glucose Leads to Apoptotic Cell Death - Mir, Shakeel U. R. (J Biol Chem, 2015)
Autophagy, a cellular recycling process responsible for turnover of cytoplasmic contents, is critical for maintenance of health. Defects in this process have been linked to diabetes. Diabetes-associated glucotoxicity/lipotoxicity contribute to impaired β-cell function and have been implicated as contributing factors to this disease. We tested the hypothesis that these two conditions affect β-cell function by modulating autophagy. We report that exposure of β-cell lines and human pancreatic islets to high levels of glucose and lipids blocks autophagic flux and leads to apoptotic cell death. EM analysis showed accumulation of autophagy intermediates (autophagosomes), with abundant engulfed cargo in palmitic acid (PA)- or glucose-treated cells, indicating suppressed autophagic turnover. EM studies also showed accumulation of damaged mitochondria, endoplasmic reticulum distention, and vacuolar changes in PA-treated cells. Pulse-chase experiments indicated decreased protein turnover in β-cells treated with PA/glucose. Expression of mTORC1, an inhibitor of autophagy, was elevated in β-cells treated with PA/glucose. mTORC1 inhibition, by treatment with rapamycin, reversed changes in autophagic flux, and cell death induced by glucose/PA. Our results indicate that nutrient toxicity-induced cell death occurs via impaired autophagy and is mediated by activation of mTORC1 in β-cells, contributing to β-cell failure in the presence of metabolic stress.